Pengaruh Komposisi Campuran Multi-Variabel terhadap Kuat Tekan Mortar Geopolimer Fly Ash-GGBFS - Novacharisma Vindiantri Verucha; Bayu Rahmat Ramadhan; Rezky Susmono Karuru; Sri Nur Akifa; Misel Boro Allo (Institut Teknologi Garut, 2026)
Growing interest in sustainable construction materials has driven the utilization of industrial by-products, such as fly ash, as alternatives to Portland cement. However, Type F fly ash typically exhibits low calcium (CaO) content, resulting in slow geopolymerization and limited strength development under ambient curing conditions. This study investigates the combined influence of Ground Granulated Blast Furnace Slag (GGBFS) incorporation and multi-variable mix composition on the compressive strength development of fly ash-based geopolymer mortar.An experimental program based on a Taguchi L9 design was employed to systematically evaluate the effects of GGBFS content (0%, 10%, 20%, and 30%), activator-to-binder ratios (0.30, 0.35, and 0.40), and aggregate-to-binder ratios (2.25, 2.50, and 2.75). Compressive strength was measured at 7, 14, and 28 days under ambient curing conditions and compared with conventional Portland cement mortar. The results indicate that GGBFS plays a dominant role in enhancing strength development by promoting the formation of hybrid C–A–S–H and N–A–S–H gels, which densify the microstructure and accelerate reaction kinetics.The fly ash-only mixture exhibited very low strength (0.82 MPa at 28 days), while mixtures incorporating GGBFS showed significant improvement. The optimal composition (D40G30A2.5) achieved a compressive strength of 28.81 MPa at 28 days, exceeding the Portland cement control (16.75 MPa). Statistical analysis further confirms that GGBFS content is the most influential parameter governing strength development, followed by activator dosage, while aggregate proportion has a relatively minor effect. This study contributes a systematic multi-parameter optimization framework for ambient-cured fly ash–GGBFS geopolymer mortar, demonstrating that 20–30% GGBFS incorporation enables practical strength development without the need for elevated temperature curing, thereby enhancing its applicability for real-world construction.